PERILAKU LENTUR BALOK BETON BERTULANG HIGH VOL-UME FLY ASH (HVFA) DENGAN VARIASI UKURAN BUTIR MAKSIMUM AGREGAT - Lianasari, Angelina Eva; Siahaan, Richardo Putra (Jurnal Teknik Sipil, 2019)
Global warming is a serious environmental issue. Production process of Portland Cement (SP) contribute 5% of all carbon dioxide emissions, the main cause of global warming and making cement means making pollution. High Volume Fly ash (HVFA) concrete technology is one solution that can be offered to overcome this problem. HVFA concrete is a type of concrete made using high enough fly ash, which is more or equal to 50% by weight of cement. In this study, the use of fly ash (FA) as a cement replacement material is about 50%. One disadvantage of HVFA concrete is the low early strength or slower, so in this study HVFA concrete was made with coarse aggregate size to smaller. This study compared HVFA concrete beams with size of aggregates are 20 mm and 4.75 mm, the planed compressive strength (f’c) is 25 MPa. Fly ash will substituted by 50% of the weight of the cement and the addition of superplasticizer about 0.4% by weight of cement. The size of specimens for flexural capacity of reinforced concrete beams about 140 x 240 mm with a span of 2000 mm. The flexural strength test arrangement with two-point loading. And the results of the study showed an increase in flexural capacity of 13.38%.